Cardiovascular health research priorities in the United Arab Emirates - Ghader, Nariman; Al-Yateem, Nabeel; Dalibalta, Sarah; Razzak, Hira Abdul; Rahman, Syed Azizur; Al Matrooshi, Fatima; Al Shaya, Sara; Al Marzouqi, Amina (Frontiers in Public Health, 2023)
Background Cardiovascular diseases (CVDs) are a leading cause of morbidity and mortality in the United Arab Emirates (UAE) and have been prioritized for intervention by healthcare authorities and clinicians. Aim To identify clinically relevant research priorities for the treatment and prevention of CVDs in the UAE. Methods This study used the nominal group technique to identify CVD-related research priorities. Participants were 37 experts from UAE hospitals, academic and research institutions, CVD associations, and paramedical organizations. Results Initially, 138 research topics were suggested by participating experts. These topics were then refined to identify the most important research priorities related to CVD prevention and treatment. The top research priority areas were: development of evidence-based, customized algorithms for CVD prevention and in-hospital emergency interventions; the availability, accessibility, and affordability of CVD treatment and rehabilitation; identification of relationships between CVDs, lifestyle factors, and mental health; efficacy and constraints in the management of cardiac emergencies; and epidemiological studies that trace CVD in the UAE. Conclusion The identified research priorities will guide a more informed research program for CVD treatment and prevention in the UAE. Funding opportunities and support for researchers should be prioritized for these identified research areas.